Increasing the Production of β-Glucan from Saccharomyces carlsbergensis RU01 by Using Tannic Acid - Natthaporn Chotigavin; Wiramsri Sriphochanart; Surachai Yaiyen; Sanya Kudan (Applied Biochemistry and Biotechnology, 2021)
Abstract In this study, we increased β-glucan production from brewer’s yeast, Saccharomyces carlsbergensis RU01, by using tannic acid. High-pressure freezing and transmission electron microscopy (HPF-TEM) revealed that the yeast cell wall obtained from yeast malt (YM) medium supplemented with 0.1% w/v tannic acid was thicker than that of yeast cultured in YM medium alone. The production of β-glucan from S. carlsbergensis RU01 was optimized in 3% w/v molasses and 0.1% w/v diammonium sulfate (MDS) medium supplemented with 0.1% w/v tannic acid. The results showed that MDS medium supplemented with 0.1% w/v tannic acid significantly increased the dry cell weight (DCW), and the β-glucan production was 0.28±0.01% w/v and 11.99±0.04% w/w. Tannic acid enhanced the β-glucan content by up to 42.23%. β-Glucan production in the stirred tank reactor (STR) was 1.4-fold higher than that in the shake flask (SF) culture. Analysis of the β-glucan composition by Fourier transform infrared (FTIR) spectroscopy showed that the β-glucan of S. carlsbergensis RU01 cultured in MDS medium supplemented with 0.1% w/v tannic acid had a higher proportion of polysaccharide than that of the control. In addition, β-glucans from brewer’s yeast can be used as prebiotic and functional foods for human health and in animal feed.
Keywords: Food composition and properties; Polysaccharides and Plant Cell Walls; Fungal Biology and Applications